Calf Diarrhea: Epidemiological Prevalence and Bacterial Load in Oyo and Ogun States, Nigeria (2016)
Diarrhea in calves is one of the most important causes of calf morbidity, mortality and economic losses. The prevalence of diarrhea in calves was studied in 12 farms in Oyo and Ogun states in South Western Nigeria. A total of 825 calves up to 6-months old were sampled over a period of 12 months with 120 (14.5%) of the calves showing signs of diarrhea. Faecal samples of diarrheic calves (n=120) were collected, and screened for bacterial pathogens using standard laboratory procedures. In Oyo and Ogun States, highest prevalence rates of calves with diarrhea were noticed in two farms of Oyo State 50% (25 out of 50 calves) and Ogun State 23% (12 out of 52 calves) were recorded respectively. Only 19 (15.8%) of the 120 calves had bacterial pathogens; Of the calves (n=19) where bacteria were isolated Escherichia coli was isolated from 12 calves (63.2%), Salmonella species was isolated from 10 calves (52.6%) and Campylobacter species was isolated from 1 calf (5.3%). The lowest levels of bacterial detection were seen in diarrheic samples from White Fulani calves (8.9%) with the highest levels seen in samples from Jersey calves (50%). Calves of 0-2 months had positivity bacterial cause of diarrhea of 18.4%, calves between 3 and 4 months had positivity of 8.8% and calves of 5-6 months had positivity of 20%. Bull calves had 17.0% positivity while heifers had 14.8% positivity among diarrheic calves. Calves having severe diarrhea had highest percentage positivity (26.1%) of bacterial isolates while calves with moderate diarrhea had the least percentage positivity (13.6%). Calves reared in semi-intensive system of management were the most susceptible (18.0%) while those reared under extensive system were least susceptible (13.6%) to bacterial scours. Therefore, Escherichia coli, Salmonella and Campylobacter organisms were most prevalent in calf scours. Age, breeds, sex, severity of diarrhea and system of management are predisposing factors of calf diarrhea.